Implementasi Program Pengembangan Kepemimpinan bagi Siswa Sekolah Menengah Atas - Wahyudi, Triyono Arief; Iskandar, Donant Alananto; Tun Ganyang, Machmed; Ritonga, Wier (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2023)
This article examines the role of leadership development for senior high school students through extracurricular programs. The initiative is designed to improve students' comprehension of leadership functions and assess their impact on personal and social growth. Employing a community service framework, the program implements extracurricular activities focused on building leadership capacity. The intervention includes leadership training sessions, group discussions, collaborative projects, and hands-on leadership experiences. Findings reveal a significant enhancement in students' leadership abilities, sense of social responsibility, engagement in school activities, and preparedness for future endeavors. These results underscore the strategic importance of extracurricular programs in cultivating leadership qualities among senior high school students.